Development of tasty marinating kit for tenderization and preservation of beef chuck - Sultana, A; Huque, KS; Amanullah, SM (Bangladesh Veterinarian, 2010)
Chuck is the biggest and one of the tougher cut of beef carcass. By improving the tenderness of chuck meat it can have a higher value to the consumer. The study was conducted to know the efficacy of tasty kit (containing 1.2 M sodium chloride, 0.25 M sodium bicarbonate and 0.1% ascorbic acid) as a meat preservation and tenderization technique during freezing. Beef chucks from four native bulls were collected from a local market and divided into two groups- one was treated with tasty kit and the other kept as control. Both the treated and untreated meats were well packed and kept in freezer at -20°C for a month. Compared to the untreated group, higher moisture content was found in treated raw and cooked meat (p<0.05). Significantly lower protein content (p<0.05) in treated cooked meat may be resulted from the solubilization of myofibrillar protein by salt and bicarbonate. Treated meat had a higher water-holding capacity (p<0.05), lower drip loss (p<0.05) and lower cook loss (p<0.01). During a sensory test, panellists gave significantly higher values for general appearance (p<0.01), flavour (p<0.05), colour (p<0.05), tenderness (p<0.01), juiciness (p<0.01) saltiness (p<0.01) and overall acceptability (p<0.01). It is suggested that tough chuck meat may be successfully tenderized with the salt-bicarbonate marinating technique before freezing. DOI: 10.3329/bvet.v26i1.4628 Bangl. vet. 2009. Vol. 26, No. 1, 23-30